Well-differentiated papillary mesothelial tumor of the fallopian tube: A case report - Kotani, Hideko; Kitazawa, Sohei; Kaneko, Hisae; Tasaka, Mie (Current problems in cancer. Case reports, 2025)
Well-differentiated papillary mesothelial tumor (WDPMT) is a rare mesothelial neoplasm that typically arises in the peritoneum of women of reproductive age and generally follows an indolent course, although occasional recurrence or malignant transformation has been reported. WDPMT of the fallopian tube is extremely uncommon. We report the case of a 46-year-old woman with long-standing menorrhagia who underwent total abdominal hysterectomy with bilateral salpingectomy for uterine leiomyomas, during which a solitary 5-mm nodule was incidentally identified on the left fallopian tube. Histological examination showed fibrovascular cores lined by cuboidal mesothelial cells with minimal atypia and no stromal invasion, while immunohistochemistry revealed WT1 and calretinin positivity, estrogen receptor and progesterone receptor negativity, weak focal PAX8 staining, and retained nuclear expression of BRCA1-associated protein 1 (BAP1) and methylthioadenosine phosphorylase (MTAP). These findings supported a diagnosis of WDPMT. This case adds to the limited literature on fallopian tube WDPMT and highlights the importance of recognizing this rare entity and considering long-term follow-up, given its generally indolent but occasionally unpredictable behavior.